2022
DOI: 10.56536/ijmres.v12i1.189
|View full text |Cite
|
Sign up to set email alerts
|

Doctors’ Attitude Toward Patient Demand and Direct-To-Consumer Pharmaceutical Advertisements in Pakistan

Abstract: Since the COVID-19 phenomenon has emerged, e-patient attitudes have created a new normal for abnormal situations. This study sees how the patient demands will affect physician persistence habits from the perspective of physician-patient relationship, which is reinforced by increased digital health advertisements such as direct to consumer pharmaceutical advertisements. In this respect, primary data was collected from 300 doctors of Peshawar, using cluster random sampling through an adapted questionnaire and ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In addition, it has been suggested that physicians exhibit either persistent or nonpersistent behavior, with infrequent modifications to their preferences. Shahzad et al (2021) have argued that the tendency to persist in habitual behavior has a robust and positive influence on physician’s prescription decisions.…”
Section: Conceptual Background and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been suggested that physicians exhibit either persistent or nonpersistent behavior, with infrequent modifications to their preferences. Shahzad et al (2021) have argued that the tendency to persist in habitual behavior has a robust and positive influence on physician’s prescription decisions.…”
Section: Conceptual Background and Hypothesis Developmentmentioning
confidence: 99%
“…It is also concluded from the moderation analysis that physician’s habit persistence has played a significant moderating effect between marketing efforts’ effectiveness and the decision of the physician to prescribe a particular medicine (Murshid et al , 2019). In the clinical realm, a physician’s habit persistence is developed over time through various factors such as clinical experience, mentorship, brand promotion and academic updates (Murshid et al , 2019; Shahzad et al , 2021).…”
Section: Introductionmentioning
confidence: 99%